Arabic Translation, Stylistic And Rhetorical: Manhood In The Hadith - Sobhy Ebrahim Elmelegy (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2023)
The main objective of this paper is to define “al-rujoolah” (manhood) and its contexts in the primary Arabic literature that it Prophet Muhammad's (peace be upon him) Hadith. The project's goal is to comprehend the significance of this subject in the Prophet's statement and to contribute to the library of Arabic rhetorical and scientific work related to this Hadith, which includes a rhetorical lesson, stylistic analysis, and reveals the ornamental characteristics and stylistic features. The study used an analytical method based on analyzing, interpreting, and comparing how the Quran and prophets talked about this trait and its signs. Also, talk about the different stories in the Hadith to figure out what they mean. The word “al-rujoolah” in